Interface modification to improve hole-injection properties in organic electronic devices - Choulis, Stelios A.; Choong, Vi-En; Patwardhan, Aditee (My University, 2006)
The performance of organic electronic devices is often limited by injection. In this paper, improvement of hole injection in organic electronic devices by conditioning of the interface between the hole-conducting layer (buffer layer) and the active organic semiconductor layer is demonstrated. The conditioning is performed by spin-coating poly(9,9-dioctyl-fluorene-co-N-(4- butylphenyl)-diphenylamine) (TFB) on top of the poly(3,4-ethylene dioxythiophene): poly(styrene sulfonate) (PEDOT:PSS) buffer layer, followed by an organic solvent wash, which results in a TFB residue on the surface of the PEDOT:PSS. Changes in the hole-injection energy barriers, bulk charge-transport properties, and current-voltage characteristics observed in a representative PFO-based (PFO: poly(9,9-dioctylfluorene)) diode suggest that conditioning of PEDOT:PSS surface with TFB creates a stepped electronic profile that dramatically improves the hole-injection properties of organic electronic devices
Keywords: Conducting polymers; Light emitting diodes; Organic electronics; Polyfluorenes